2009
DOI: 10.1590/s0100-40422009000700023
|View full text |Cite
|
Sign up to set email alerts
|

Hidrocarbonetos e esterois como indicadores de fontes e destino de matéria orgânica em sedimentos da Baía de Sepetiba, Rio de Janeiro

Abstract: Recebido em 15/9/08; aceito em 11/3/09; publicado na web em 4/8/09 HYDROCARBONS AND STEROLS AS INDICATORS OF SOURCE AND FATE OF ORGANIC MATTER IN SEDIMENTSFROM SEPETIBA BAY, RIO DE JANEIRO. The inputs of organic matter derived from natural and anthropogenic sources to Sepetiba Bay were investigated by using aliphatic hydrocarbons and sterols in superficial sediments. Concentrations ranged from 0.26 to 2.65 μg g -1 , <0.01 to 17.41 μg g -1 and 0.77 and 9.24 μg g -1 for n-alkanes, UCM (unresolved complex mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 26 publications
1
7
0
9
Order By: Relevance
“…Total ion current chromatogram (TIC) extracted at mass 57 support the presence of TPH (see Fig 4). The highest levels of TPH in mussels were found during 2004 (61-287 µg g -1 d.w.) which is coincident with the highest levels found in sediments, and they are higher than chronically mildly polluted areas such as Todos os Santos Bay (42 µg g -1 ) 45 and Sepetiba Bay, Brasil (0.26-2.65 µg g -1 ) 46 , Westernport, Australia (126 µgg 1 ) 47 , Narragansett Bay, Rhode Island (42 µg g -1 ) 48 , the Amposta Offshore Oil Production Plataform, Western Mediterranean (40 µg g -1 ) 49 and Gulf of Naples (48 µgg -1 wet weight)…”
mentioning
confidence: 57%
“…Total ion current chromatogram (TIC) extracted at mass 57 support the presence of TPH (see Fig 4). The highest levels of TPH in mussels were found during 2004 (61-287 µg g -1 d.w.) which is coincident with the highest levels found in sediments, and they are higher than chronically mildly polluted areas such as Todos os Santos Bay (42 µg g -1 ) 45 and Sepetiba Bay, Brasil (0.26-2.65 µg g -1 ) 46 , Westernport, Australia (126 µgg 1 ) 47 , Narragansett Bay, Rhode Island (42 µg g -1 ) 48 , the Amposta Offshore Oil Production Plataform, Western Mediterranean (40 µg g -1 ) 49 and Gulf of Naples (48 µgg -1 wet weight)…”
mentioning
confidence: 57%
“…6 No Brasil, os estudos que usam coprostanol e outros esterois fecais na avaliação da contaminação fecal em áreas costeiras são ainda relativamente recentes, sendo a grande maioria deles relativos às regiões sul-sudeste do país. [8][9][10][11][12][13][14][15] No geral, esses trabalhos confirmam a aplicabilidade do coprostanol como indicador fecal em regiões tropicais. Por outro lado, sugerem que a geoquímica dos esterois fecais pode ser afetada pela elevada atividade microbiana em altas temperaturas e, desta forma, os índices de contaminação fecal definidos para regiões temperadas 6,16 devem ser aplicados com cautela em regiões tropicais.…”
Section: Introductionunclassified
“…Alternatively, the low C 17 /Pr and C 18 /Ph can be result of a higher input of pristane and phytane. According to Ten Haven et al, 65 the interpretation of these ratios sometimes may not be reliable due to the wide variety of sources for these isoprenoid compounds.Comparing these results with other degraded environments, 7,[66][67][68][69] it is observed that, although these samples exhibit intermediate values for the total n-alkanes, UCM concentrations are higher than in most other regions. Significantly higher concentrations of UCM were found by Wagener et al 30 near the station P2, which may indicate heterogeneity of the bay sediments that can be explained by the action of the tides in the remobilization and transport or even by dredging activities and sediment transport to outside the bay.…”
mentioning
confidence: 76%